FAKTOR YANG MEMPENGARUHI MOTIF SOSIAL – EKONOMI MELALUI KEPUTUSAN BERZAKAT MENGGUNAKAN LAYANAN DIGITAL (STUDI KASUS LAZ AL AZHAR) - Arifah Khairrani; Sri Indah Nikensari; Dicky Iranto (Yayasan Education and Social Center, 2022)
As a country with the largest Muslim population in the world, there is excellent potential for Islamic financial instruments for the prosperity of the people, one of which is Zakat as an instrument of income distribution that can be the answer to problems that are visible in Indonesia, economic and social. Zakat itself has complete laws and instruments, but the potential and reality of its collection are still reversed. This study describes the conditions of collecting Zakat and the factors influencing muzakki's decision on digital Zakat. Using the Analytical Network Process (ANP) method, the factors influencing muzakki's decisions are trust, ease of use, and zakat literacy. The results of this study indicate that trust, ease of use, and zakat literacy affect the decision of muzakki to pay Zakat digitally. The first result shows that the ease of use factor has the most considerable influence on the decision of the digital Zakat and the most influential sub-factor is flexibility